Tai biến trượt lở sờn tại thị xã Hà Giang và vấn đề cảnh báo - An, Lê Đức; Khanh, Uông Đình; Tuấn, Tống Phúc; Thành, Nguyễn Ngọc (Vietnam Journal of Earth Sciences, 2008)
Landslide hazard in Ha Giang town and problem of prediction